DESENTRALISASI KEKUASAAN DAN KEBERLANJUTAN PERADABAN: STUDI HISTORIOGRAFIS ATAS DINASTI-DINASTI ISLAM TIMUR - Latifa, Azzahra Sindhi; Manshur, Hamim Sirojuddin Al; Sari, Fina Thazha Eka; Imamma, Arifah Nur; Istiqomah, Aginra Falah; Hakiman, Hakiman (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
ABSTRACT The post-Abbasid period is often framed as a phase of decline due to the weakening of political authority in Baghdad. However, this perspective does not fully capture the dynamics in the eastern regions, which in fact experienced significant developments across various domains. This study aims to examine the role of political decentralization as a transformative mechanism that sustained the continuity of Islamic civilization during this period. It employs a qualitative approach based on library research, utilizing a historiographical-critical analysis of recent academic sources. The focus is placed on the dynamics of regional dynasties in the eastern Islamic world that contributed to changes in political, intellectual, and cultural structures. The findings indicate that the decline of central authority did not lead to stagnation, but instead facilitated the emergence of new centers that were active in advancing knowledge, economic activity, and religious life. Decentralization enabled a balance between political authority and religious legitimacy, while also expanding intellectual networks through local patronage and cultural adaptation. These findings suggest that the post-Abbasid period is more appropriately understood as a phase of adaptive transformation, characterized by the restructuring of power, diversification of civilizational centers, and socio-cultural integration. Accordingly, this study contributes to strengthening a resilience perspective in Islamic historiography, emphasizing continuity rather than decline. ABSTRAK Periode pasca-kejayaan Abbasiyah sering diposisikan sebagai fase kemunduran akibat meredupnya otoritas politik di Baghdad. Perspektif tersebut belum sepenuhnya menjelaskan dinamika di kawasan Timur yang justru menunjukkan perkembangan signifikan dalam berbagai bidang. Penelitian ini bertujuan mengkaji peran desentralisasi kekuasaan sebagai mekanisme transformasi yang menopang keberlanjutan peradaban Islam pada periode tersebut. Penelitian menggunakan pendekatan kualitatif berbasis studi kepustakaan dengan analisis historiographical-critical terhadap berbagai sumber akademik mutakhir. Fokus kajian diarahkan pada dinamika dinasti-dinasti regional di kawasan Timur yang berkontribusi dalam perubahan struktur politik, intelektual, dan kultural. Hasil penelitian menunjukkan bahwa melemahnya pusat kekuasaan tidak mengakibatkan stagnasi, melainkan mendorong lahirnya pusat-pusat baru yang aktif dalam pengembangan ilmu pengetahuan, ekonomi, dan praktik keagamaan. Desentralisasi memungkinkan terbentuknya keseimbangan antara otoritas politik dan legitimasi religius, sekaligus memperluas jaringan keilmuan melalui patronase lokal dan adaptasi budaya. Temuan ini menegaskan bahwa periode pasca-Abbasiyah lebih tepat dipahami sebagai fase adaptive transformation yang ditandai oleh restrukturisasi kekuasaan, diversifikasi pusat peradaban, dan integrasi sosial-budaya. Dengan demikian, penelitian ini berkontribusi dalam memperkuat perspektif resilience dalam historiografi Islam yang menekankan kesinambungan, bukan kemunduran.